2007
DOI: 10.1039/b610018j
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating fluorescein using adipic acidself-assembly on the surface of PPI-3 dendrimer

Abstract: A water-soluble self-assembly has been formed by associating adipic acid molecules onto the surface of the third generation poly(propyleneimine) dendrimer and this system has been used to encapsulate fluorescein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 19 publications
0
51
0
1
Order By: Relevance
“…When adding ZnTPPC 4-more than 8 times greater molar ratio to the dendrimer, a dark solid, which is formed by the ion-association between G4 PAMAM dendrimer and ZnTPPC 4-, was spontaneously precipitated in the aqueous solution, and the absorption spectrum indicated the presence of excess of free ZnTPPC 4-molecules. In the case that the fluorescent species is encapsulated in the interior of dendrimers, the fluorescence quenching of dye species takes place effectively [21,22]. The emission intensity observed in the present condition (molar ratio = 1:1)…”
Section: Spectroelectrochemical Analysismentioning
confidence: 78%
“…When adding ZnTPPC 4-more than 8 times greater molar ratio to the dendrimer, a dark solid, which is formed by the ion-association between G4 PAMAM dendrimer and ZnTPPC 4-, was spontaneously precipitated in the aqueous solution, and the absorption spectrum indicated the presence of excess of free ZnTPPC 4-molecules. In the case that the fluorescent species is encapsulated in the interior of dendrimers, the fluorescence quenching of dye species takes place effectively [21,22]. The emission intensity observed in the present condition (molar ratio = 1:1)…”
Section: Spectroelectrochemical Analysismentioning
confidence: 78%
“…In particular for cross peaks C, strong NOE interactions between the aromatic protons (1‐H, 2‐H and 3‐H) and methyl protons (8‐H) of phenylbutazone and methylene protons (a‐H and c‐H) of G6 PAMAM dendrimer are observed, while weaker NOE interactions between aromatic and methyl protons of drug and b‐H and d‐H of dendrimer is obtained, indicating that the aromatic and methyl groups of phenylbutazone localize near the a‐H and c‐H of PAMAM dendrimer (Scheme b). It is known that the NOE interaction between protons is distance‐dependent, and the larger the distance between the protons, the less efficient the NOE interaction can be observed 44. Since the NOE interactions between protons separated by more than 5 Å can not be detected, the cross peaks C in Figure 4 should not from phenylbutazone molecules attached on the surface of G6 PAMAM dendrimer by electrostatic interactions.…”
Section: Resultsmentioning
confidence: 98%
“…2D‐NOESY measurements can provide information on the distance between protons in close spatial proximity within a given molecule and can also be used to detect the host–guest interactions in solutions 41–45. This technique was employed in this study to further investigate the interaction details between dendrimers and phenylbutazone molecules.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 ] Since this process is highly pH dependent, [ 34 ] we optimized the pH for doping two NR molecules in one PAMAM, for NR, doping more than two molecules was not possible. After varying different solvents, elevated temperatures, pH etc., it is found that at >pH 9.0 the NR molecules get encapsulated inside the dendritic cavities at 300 K. The optimization process and all other synthetic characterization details are in the supporting information online text along with Figure S5 (Supporting Information) where we have plotted the number of NR from mass variation data of PAMAM versus NR-PAMAM along with the pH of the solution.…”
Section: Methodsmentioning
confidence: 99%